THE ROLE OF ISLAMIC SPIRITUALITY IN INDUSTRIAL TRAINING FOR AGRICULTURAL STUDENTS - Rozlianah Fitri Said,; Musaiyadah Ahmadun,; Nur Aziemah Jasni, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The spiritual aspect is an essential element that needs to be emphasised among today's university students. It can shape their behaviour, actions, and decisions. Therefore, the main objective of this study is to identify the extent to which the programs conducted by the Faculty of Plantation and Agrotechnology can shape the spiritual values of students before they undergo industrial training outside the campus through placement in agricultural and plantation agencies throughout Malaysia. The Universiti Teknologi MARA (UiTM) Sabah Branch, Kota Kinabalu campus, was selected as the case study organisation for this qualitative study. 13 students participating in the program conducted by the Faculty of Plantation and Agrotechnology who were interviewed using a semi-structured format. Thematic data analysis was used to analyse the collected data. Overall, the findings of the qualitative study show that the program or activity carried out plays a role in increasing the spiritual value of students in terms of mujahadah al-nafs and fostering the character of al-ihsan.